Етимологічна інтерпретація деяких мікротопонімів поліського села Липне - Громик, Юрій Васильович; Hromyk, Yu. V. (Університет Марії Кюрі-Склодовської (Люблін, Польща), 2005)
Виконано лінгвістичний аналіз структури, семантики та етимології деяких мікротопонімів села Липне, що розташоване на межі західної і центральної частин Українського Полісся. Установлено, що місцеві топоніми виразно відбивають особливості говірки, а також специфіку ландшафту, історію заселення території і зв’язки поліщуків з іншими етносами.In the article the linguistic analysis of the structure, semantics and etymology of some microtoponyms of the village of Lypne, situated on the borderline of the western and central parts of Ukrainian Polissya, is performed. The heterogeneity of such names as to their origin, structure and semantics is stated. It is revealed that the local toponymy distinctly reflects the peculiarities of the dialects as well as the specificity of the landscape, the land colonization history and the relationship of the Polissyan population with other ethnoses.
Etymological Interpretation of Some Microtoponyms of the Polissyan Village of Lypne
Keywords: мікротопонім; microtoponym; етимологія; etymology